Chemical Ordering of Ag-Au Alloys in the Molten State - Koirala, Ishwar (Journal of Institute of Science and Technology, 2018)
Simple statistical model has been used to report the thermodynamic, structural, transport and surface properties of liquid Ag-Au alloys at 1350K. In thermodynamic properties we have studied the free energy of mixing, heat of mixing, entropy of mixing and the chemical activity of both components of the alloys. For the structural investigation, our study includes concentration fluctuation in long wave length limit and Warren-Cowley short range order parameter. Viscosity and diffusivity of the alloys have been studied to understand transport properties. The surface behavior has been analyzed by computing surface concentration and surface tension of the alloys. The structural behaviors of the alloys are found to be symmetric with respect to concentrations of the species. The computed results are in good agreement with experimental data. Positive deviation of viscosity isotherms from linear law is observed. Surface tension of the alloys is found to be smaller than ideal values throughout bulk concentration of silver. For all theoretical analysis, concentration independent energy parameter takes important role, which is found to be temperature dependent and finally analysis confirms that presented alloy is hetero-coordinated. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 191-201